Mass-balance changes of the debris-covered glaciers in the Langtang Himal, Nepal, from 1974 to 1999 - Pellicciotti, Francesca; Stephan, Christa; Miles, Evan; Herreid, Sam; Immerzeel, Walter W.; Bolch, Tobias (Journal of Glaciology, 2015)
ISSN:0022-1430 ISSN:1727-5652